Fear of Covid-19 among nurses in University Malaya Medical Centre: The prevalence and its association with anxiety, depression and the coping strategies / Farah Nabila Abd Majid - Farah Nabila, Abd Majid (2021)
Introduction: The current COVID-19 pandemic has significantly caused an escalation in mental health issues among nurses. Aim: This study aims to determine the level of fear of COVID-19 and its association with socio-demographic factors, COVID-related factors, coping styles, anxiety and depression. Methods: A cross-sectional study was conducted via online survey. A total of 814 nurses from various disciplines in UMMC, a tertiary teaching hospital in Malaysia participated in the study. Sociodemographic data, COVID-related data and a set of validated questionnaires were used to measure fear of COVID-19, anxiety, depression and coping strategies. Results: The prevalence of highlevel fear of COVID-19, anxiety symptoms and depressive symptoms were 71.5%(n=582), 21.0%(n=171), and 17.9%(n=146), respectively. Providing care to nonCOVID-19 patients significantly predicted higher level of fear of COVID-19 (adjusted OR of 1.55, 95% CI 1.06-2.28, p<0.05). Nurses who perceived increased in their work burden was significantly associated with fear of COVID-19 (adjusted OR 0.61, 95% CI 0.43-0.89, p<0.05), anxiety (adjusted OR 0.44, 95% CI 0.26-0.76, p<0.05) and depression (adjusted OR 0.56, 95% CI 0.32-0.89, P<0.05). Fear of COVID-19 was positively correlated with both anxiety and depression with r value of 0.49 and 0.39, respectively. Avoidant coping strategy was significantly and positively correlated with all three psychological complications which were fear of COVID-19, anxiety and depression, with a coefficient of correlation, r, of 0.29, 0.46 and 0.27, respectively. Conclusion: There was a high level of fear of COVID-19 among nurses. Nurses who did not provide direct care and had increased work burden were more fearful of COVID-19. Using avoidant oriented coping was associated with negative psychological outcome. Thus, strategies to address psychosocial issues and enhance effective coping skills among nurses should be implemented to prevent detrimental psychological outcome amongst nurses regardless of whether they are providing direct or non-direct care to COVID-19 patients. iv Keywords: fear, COVID-19, anxiety, depression, coping, nursing, mental health